Pathways between Eastern and Western education - Hudson, John P. W. (Emerald Publishing Limited : IAP, Information Age Publishing, 2009)
Educators everywhere will want their hands on this book! Cover to cover, this book delivers on showing exactly what the title says: pathways between Eastern and Western education systems. Why will you want to buy this book?Readers will love the idea that different systems have a lot to share. Through a blend of anecdotes and clear information, Hudson paints a vivid picture of both systems, and provides plenty of opportunity to explore child-centered education, differentiated learning, curriculum, assessment, and a lot more. There's lots of strategies to try out Monday morning, or sit with a coffee for a few hours to think about your practice, and where you have room to grow.Plenty of new ideas pepper the book. From a fresh new take on what learning is to the power of assessment, there's plenty here for refreshing debate.Hudson's view takes in a wide swath: truly big ideas from a 35,000 foot viewpoint! Would you be able to sum up the two systems in ten words or less? From the very first page, you'll be keen to see how!Parents, veteran teachers, administrators, politicians, students of education, all will find plenty to think about here, and lots to talk about.Hudson wants us all to take a refreshing new pathway to growth in education, whether we are Eastern, Western, young or old.This is your book; see what everyone is talking about and get excited about education again!